The Effects of Different Fertilizer on the Resistance of Tomato in Tomato Yellow Leaf Curl Virus (TYLCV) - Barrera, Janet; Fuentes, Mariecel (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The study aims to determine the resistance and evaluate the cost effectiveness of different organic fertilizer in tomato against Tomato Yellow Leaf Curl Virus (TYLCV). Four types of treatments were used, namely: Canaan Organic Fertilizer, Idol Organic Fertilizer, Synthetic Fertilizer and no fertilizer applied as control group. This study found that Treatment 4 (Synthetic Fertilizer) shows the highest height, least symptoms of TYLCV (yellowing and curling of leaves), and highest yield of tomatoes among the other treatments. Tomatoes applied with different fertilizers had no effect on the resistance against the Tomato yellow leaf curl virus. Once B. tabacci is present on the tomato host, there is a great chance of disease incidence.